2023
DOI: 10.3389/fpls.2023.1193668
|View full text |Cite
|
Sign up to set email alerts
|

Keystone microalgae species determine the removal efficiency of sulfamethoxazole: a case study of Chlorella pyrenoidosa and microalgae consortia

Abstract: In recent years, antibiotics pollution has caused serious harm to the aquatic environment, and microalgae mediated degradation of antibiotics has attracted increasing attention. However, the potential toxicity of antibiotics to keystone microalgae species or their microalgae consortia, and the impact of microalgal diversity on antibiotic removal need to be further studied. In this study, we investigated the removal efficiency and tolerance of five freshwater microalgae (Chlorella pyrenoidosa, Scenedesmus quadr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…14 Huang et al observed a diminished antibiotic removal performance in mixed microalgae media compared to single microalgae media, attributed to metabolic competition. 15 Therefore, MBGS formation with a proficient exogenous microalgal strain under a relatively low light intensity for antibiotic treatment could increase the system performance and efficiency. There is currently limited research on the fate of antibiotics and ARGs in MBGS systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Huang et al observed a diminished antibiotic removal performance in mixed microalgae media compared to single microalgae media, attributed to metabolic competition. 15 Therefore, MBGS formation with a proficient exogenous microalgal strain under a relatively low light intensity for antibiotic treatment could increase the system performance and efficiency. There is currently limited research on the fate of antibiotics and ARGs in MBGS systems.…”
Section: Introductionmentioning
confidence: 99%
“…In MBGS development, uninoculated BGS exposed to a stronger light promoted the growth of diverse microalgae colonies on BGS, , while microalgae-inoculated BGS under lower light conditions fostered a quasi-unicellular microalgal growth on MBGS, enhancing stability and nutrient removal . Huang et al observed a diminished antibiotic removal performance in mixed microalgae media compared to single microalgae media, attributed to metabolic competition . Therefore, MBGS formation with a proficient exogenous microalgal strain under a relatively low light intensity for antibiotic treatment could increase the system performance and efficiency.…”
Section: Introductionmentioning
confidence: 99%